Kuvvetli deprem hareketlerinde normalizasyon spektrum üzerine etkileri - Tunay, Ş. Başaran (Fen Bilimleri Enstitüsü, 1992)
İlk çağlardan beri, insanlığın korkulu rüyası olan deprem günümüzde de gün celliğini, arttırarak korumaktadır. Dünya nüfusunun hızla artması ve büyük yerle şim bölgelerine doğru bir akının doğması nedeniyle kentler büyümüş; bunun so nucu olarak da yer sorunu ortaya çıkmıştır. Bu nedenle yapı sistemleri daha bü yük ve daha kompleks bir hale gelmiştir, Bir başka deyişle insanoğlu için dep rem riski daha da artmıştır. Bu yüzden deprem olayını tam olarak çözümlemek ve depreme dayanıklı yapı sistemleri oluşturmak zorunlu hale gelmiştir. Bunu başarmak için de hassas bir tasarımın yapılması en önemli şart olmuştur. Bu nedenle çalışmamızda, bir sismik bölgede inşa edilecek yapı sistemine deprem nedeniyle gelecek yatay etkileri veren, tasarım spektrumlanm elde et mek ana amaç olmuştur. Bunun için öncelikle, en doğru deprem verilerinin kul lanılması gerektiğinden elimizdeki hatalı kayıt edilmiş Türk Deprem verileri için ta ban hattı düzeltmesi yapılmış değerler elde edilmiştir. Bunlar için karşılık spek- trumları çizilmiş ve taban hattı düzeltmesinin etkisi araştırılmıştır. Yüksek emniyetli yapı tasarımı yöntemlerinde kullanılacak, depremi en iyi karakterize edecek deprem şiddet parametresi istatistik bir yöntem kullanılarak elde edilmiştir. Son olarak da yumuşak bir zemine ve yüksek manyitüde sahip olan Erzurum-Kars depremi ile, yine yüksek manyitüde sahip ve kayalık zeminde meyddna gelmiş olan Dursunbey depremi için bölge tasarım spektrumları çizilmiş, ve El Centra için elde edilmiş olan spektrum ile karşılaştırılarak ve bazı sonuçlara varılmıştır.

Earthquake is the biggest disaster that effect to people life for centuries. Because of sudden exist and causing big destroys, it has made symptoms made people frightened and wondered. Because of lots of people's death and big material casualties, earthquake has become the important subject to examine, since ancient civilizations for many centuries. The main aim at first investigations is to find its reasons and symptoms before formation. After years, the contains of this investigations were made more extensive and more scientific results were found about earthquakes. Because of the increasing of world population and fast modernization higher systems have to be used. In this way, earthquakes have become more dangerous for these systems, As a result of this, the projection of building higher and more reliable systems against earthquakes has been existing. For this projection earthquake must be examined more carefully and found the factors that effect to earthquakes. The earthquake investigation has begun with taking earthquake records. To have these records without errors, continuing of investigation has very big importance. The errors that made in records, caused to not to give real datums. For this reason, the errors in earthquake records must be corrected carefully. The most of errors that were made, is the sepercrting of earthquake record from "zero" line, and not to record uniform. This error effects earthquake record values wholly. Especially there exists big differences in displacement and velocity of earthquakes. To correct this wrong records, surface features have to be corrected. The earthquakes that were used in my works are given at table 1. As a first step in this investigations for the Turkish earthquakes records which the base line done or not, was drawn response spectra (for accelerations) for the investigation of effects of base line. When we compare this two-type response spectra that were drawn, we saw that, the values in response spectra that were drawn for the datums that have corrected line, are bigger. In other words, it was seen that bigger response values were found smaller, because of wrong records, and this is one of the important points that were found out in my investigations. The other subject in project against earthquakes is to choose the best parameter that symbolizes the earthquake. Table 1 As a second step in my investigation to apply the comparative way between the parameters given below to find out the best parameter that symbolizes the earthquake. The parameters that we used; a) Maximum acceleration (a max) The parameter a max is the absolute maximum acceleration level during the earthquake duration. In most of dynamic analyses, average response spectrum is based on this parameter. VII b) Root-mean square intensity (RMS) Average amplitude upon duration of strong motion can be obtained by this method, But structural responses are not directly related. Root-mean square intensity is defined as: RMS = [l/t,/(Z)2dt] m Z = Ground motion acceleration o t = Duration of motion The root of square aceeleration parameter Jjs related to the total power of an earthquake acceleration. c) Root-square intensity By taking the integration of the square amplitude for the earthquake duration and by taking the square root of this integrated values another characteristic value is obtained. RS t 1/2 = [/z2(t)dt] Since the root-mean square acceleration Irms represents an average energy of earthquake acceleration, the difference between the effects by an impact type of acceleration and by an acceleration with a long duration and with small amplitudes. Now we describe the statistic way: we apply to choose the best parameter from these. We know that before, response spectrum is a curve of maximum response of single degree of freedom system with viscous damping coefficient and natural period (T), against earthquake acceleration as input. We can define the response spectrum in other shape that response spectrum is a compound function of dynamic proporties as damping coefficient and T and of input properties such as magnitude, maximum acceleration, depth of earthquake, epicentral distance, time duration and ground properties. In other words, we can say that the above reasoning allows are to express response spectrum as a compound function input properties and structural dynamic properties, Now, we consider that a be a parameter of earthquake intensity and Sa be the normalized response spectrum by this parameter. If a reflects effectly the above input properties and the normalized spectrum Sa by a parameter can be dependent upon only structural properties, Therefore, such a parameter a if found, can be the best representative of earthquake characteristics. Consequently, the normalization gives a set of stastically equivalent response spectrum. IIX As a summarized, optimum earthquake intensity parameter should be as follows: a)The parameter a includes, input properties (magnitude, depth of earthquake, epicentral distance, maximum acceleration, ground properties etc.). In other words, the normalized response spectrum Sa should least influenced by input properties. b)The parameter a should be such that, theoretical upper bound of meaningful engineering sense can be found for the response spectrum Sa normalized by the parameter by a. The above condition (b) becomes of great importance when the combinational use of a and the theoretical bound is applied for a highly reliable seismic design of structure in a probabilistic sense. After determining the properties of parameters, to find out this parameter, we use the prediction criter given below: 1 ) The best parameter should be such as to give the least value of the coefficient of variation of a set of normalized response spectrum Sa, 2) The best parameter should be such that the parameter a and the normalized response spectrum Sa are least correlated. We can easily understand that, the response spectrum, normalized with the best parameter must be independent of input properties and it becomes functions dynamic structural properties as damping coefficient and natural period. From this, we can say that the variation coefficient will be small between Sa and cf, As a result of this statistical investigation, we saw that, the maximum acceleration parameter is the best appropriate parameter for small periods. And we saw that Irs parameter is the most appropriate parameter for long periods, In first parts, we determined that the earthquake force caused vibrations and dynamic deformations in building systems. For this reason, we determined that the effects that can be effective after earthquake must be found out very carefully. Design spectra help us in determining the earthquake force that can be effective to building system that will build by an evident probability. To have design spectrums, firstly the the works that are given below must be examined. IX a) A quantitive evaluation of the seismicity of the region. This requires first to determine seismic activity levels associated with given volumes of the earth crust or with geologic features that can be identified as potential earthquake sources, such as active faults, which implies determination of the parameters of assumed probability disributions modeling edrthquake magnitudes and rates of occurence. Then, by means of attenuation expressions relating the desired ground motion characteristics (peak acceleration, velocity etc.) to earthquake magnitude anq distance to the source, the seismic risk at the site is obtained by integration of the contributions of all significant source, and expressed in term of probabilities of exceedance of given intensities during given periods of time. b) Geological evidence must also be considered in the evoluation of seismicity. As a result of investigations made for seismic area, we determine maximum velocity and displacement cccording to moximum deceleration by using ad/v2 and v/a ratios. The ad/v2 and v/a values that were determined for Turkish earthquakes are given at Table 2. Table 2 As you see the ad/v2 ratio between components is very different in impact type earthquakes. After determining these ratios, we draw the response spectrum having three parts that can be determined at the same axis team which are related to velocity, displacement and frequency, From these spectrums we saw that, the system spectrums are close to acceleration for rigid systems and displacement of ground for flexible systems. In both three spectrums that we draw, system acceleration response spectrum values are close to ground acceleration in big frequency values. In addition to this, the displacement spectrum of systems are close to ground displacement in small frequency values. After determining the frequency areas where the spectrum values are constant, by using ad/v2 and v/a ratios, we determined velocity and displacement values, And then for the earthquakes that we have examined, for a constant damping and period values, we determine the values that contain %50, %84.1 surpass probability values for acceleration, velocity and displacement response spectrum. Thus, magnification values having probability %84.1 are multiplied with the velocity and displacment values of ground that we determined from ad/v2 and v/a ratios. At last step, design spectrums are determined by using these new values for the system. As a result of our investigations, the results that we determined are given below: 1 ) At first part of our work, that is for determining the design spectra " How a little error at earthquake records effects to result, was seen. For this reason, first of all we draw the spectrums of the Turkish earthquakes recorded wrong and then we draw the spectra of the Turkish earthquakes having corrected records. Then we saw very big differences between two spectrums that we drew before. Especially the drawn spectra, with the datums that were corrected spectra, we saw the values are bigger. And we saw the system response are getting bigger. 2) As a result of investigation that we made in second pdrt of our work. We saw that we can use the reliable earthquake intensity parameter as big acceleration for small periods and Irs parameter for peak periods. We understood by controlling the acceleration values of the earthquakes that we use. 3) At the last part we determined the design spectrums for Erzurum and Dursunbey earthquakes. We saw that the design spectra are wholly related with soil conditions.
The Normalization and the effects of normalization on spectrum
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1992
Keywords: Deprem; Normalleştirme; Spektrum; Yapı sistemleri; Earthquake; Normalization; Spectrum; Structure systems